Getting in touch with your senses: Mechanisms specifying sensory interneurons in the dorsal spinal cord. Issue 5 (25th February 2021) - Gupta, Sandeep; Butler, Samantha J.
Abstract: The spinal cord is functionally and anatomically divided into ventrally derived motor circuits and dorsally derived somatosensory circuits. Sensory stimuli originating either at the periphery of the body, or internally, are relayed to the dorsal spinal cord where they are processed by distinct classes of sensory dorsal interneurons (dIs). dIs convey sensory information, such as pain, heat or itch, either to the brain, and/or to the motor circuits to initiate the appropriate response. They also regulate the intensity of sensory information and are the major target for the opioid analgesics. While the developmental mechanisms directing ventral and dorsal cell fates have been hypothesized to be similar, more recent research has suggested that dI fates are specified by novel mechanisms. In this review, we will discuss the molecular events that specify dorsal neuronal patterning in the spinal cord, thereby generating diverse dI identities. We will then discuss how this molecular understanding has led to the development of robust stem cell methods to derive multiple spinal cell types, including the dIs, and the implication of these studies for treating spinal cord injuries and neurodegenerative diseases. This article is categorized under: Neurological Diseases > Stem Cells and Development Abstract : Developmentally guided strategies to generate different populations of stem‐cell derived spinal sensory interneurons